Revision of the Hawaiian endemic leaf-mining moth genus Philodoria Walsingham (Lepidoptera: Gracillariidae): its conservation status, host plants and descriptions of thirteen new species - Kobayashi, Shigeki; Johns, Chris A.; Kawahara, Akito Y. (Zootaxa, 2021)
Philodoria Walsingham, 1907 is a threatened, Hawaiian endemic genus of leaf-mining gracillariid moths that feeds as larvae on many threatened and endangered Hawaiian endemic plants. These moths are poorly studied and species lack detailed descriptions of morphology, distribution data, and natural history information of adults and immatures. Based on extensive fieldwork from 2013 to 2016, and examination of museum specimens, we describe or redescribe 51 species, 13 which are new species and provide biological and distribution data for 41 species. The 13 new species and their host plants are: P. alakaiensis Kobayashi, Johns & Kawahara, sp. n. (Asteraceae: Dubautia sp.), P. funkae Kobayashi, Johns & Kawahara, sp. n. (Asteraceae: Wilkesia gymnoxiphium), P. haelaauensis Kobayashi, Johns & Kawahara, sp. n. (Urticaceae: Pipturus albidus, P. rockii, Pipturus sp.), P. hesperomanniella Kobayashi, Johns & Kawahara, sp. n. (Asteraceae: Hesperomannia arborescens and H. swezeyi), P. keaensis Kobayashi, Johns & Kawahara, sp. n. (host unknown), P. keahii Kobayashi, Johns & Kawahara, sp. n. (Asteraceae: Remya mauiensis), P. knudseniiella Kobayashi, Johns & Kawahara, sp. n. (Asteraceae: Dubautia knudsenii subsp. nagate and D. latifolia), P. lama Kobayashi, Johns & Kawahara, sp. n. (Ebanaceae: Diospyros sandwicensis and/or D. hillebrandii), P. limahuliensis Kobayashi, Johns & Kawahara, sp. n. (Malvaceae: Hibiscus waimeae subsp. hannerae), P. napaliensis Kobayashi, Johns & Kawahara, sp. n. (Ebanaceae: Diospyros sandwicensis and/or D. hillebrandii), P. obamaorum Kobayashi, Johns & Kawahara, sp. n. (Urticaceae: Pipturus albidus, Pipturus sp.), P. opuhe Kobayashi, Johns & Kawahara, sp. n. (Urticaceae: Urera kaalae and U. sandvicensis) and P. platyphylliella Kobayashi, Johns & Kawahara, sp. n. (Asteraceae: Dubautia platyphylla). Types of 30 species were examined, lectotypes of 16 species are designated, and a key to all Philodoria species and all Hawaiian leaf-mining moths are provided. We also present a new Hawaiian name for Philodoria, which we call Hunelele ʻelilau, meaning “tiny flier, leaf excavator”, referring to their life history and behavior. Philodoria feeds on five herbraceous and woody host plant families, and 41 species persist in localized populations in Hawaii as of 2016. Twelve species (P. alakaiensis, P. funkae, P. haelaauensis, P. hespermanniella, P. kauaulaensis, P. keaensis, P. keahii, P. knudsniiella, P. limahuliensis, P. platyphylliella, P. sciallactis, P. wilkesiella) appear to be severely threatened, as these species are rare or feed exclusively on plants that are endangered or rare. We were unable to document 10 species (P. costalis, P. lipochaetaella, P. micropetala, P. nigrella, P. nigrelloides, P. opuhe, P. pipturiana, P. pipturicola, P. pittosporella, P. spilota) after many efforts to sample in or near their historical habitats. We believe these species may be extinct. Given their restricted distribution and the fact that many species feed on rare and endangered plants, there is a risk that many more Philodoria species may go extinct unless immediate conservation measures are taken.